Impact of Plants in Isolation: The EDEN-ISS Human Factors Investigation in Antarctica - Schlacht, Irene Lia; Kolrep, Harald; Schubert, Daniel; Musso, Giorgio (Springer, 2019)
The EDEN-ISS is a greenhouse project at the Neumayer Station III in Antarctica. For the first time, this greenhouse supplied the station with fresh food and enabled research regarding sustainable and autonomous food production from Earth to Space. To investigate the plants’ impact on the crew (biophilia), a debriefing, questionnaires, and behavioral observation were used. The results show that the crew was satisfied with the consumption of fresh vegetables, which are usually not available in Antarctica. All (9 of 9 crew members) also agreed on the positive psychological and physiological impact of the plants on their well-being. The investigation will be repeated with the next crew of the Neumayer Station III and will also be proposed for comparison at stations like Concordia.